IMPLEMENTATION OF THE TRANSITION FROM THE 2013 CURRICULUM TO THE INDEPENDENT CURRICULUM IN THE HISTORY SUBJECT AT SMAN 12 PEKANBARU: Implementasi Transisi Kurikulum 2013 Ke Kurikulum Merdeka Pada Mata Pelajaran Sejarah di SMAN 12 Pekanbaru - Della Sariahni Girsang; Ahmal; Suroyo (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study discusses the implementation of the transition from the 2013 Curriculum to the Merdeka Curriculum in history learning at SMAN 12 Pekanbaru. The objectives of this study are: (1) to understand the planning, (2) to understand the implementation, and (3) to understand the evaluation of the curriculum transition from the 2013 Curriculum to the Merdeka Curriculum in the history subject at SMAN 12 Pekanbaru. This research uses a qualitative method, with data collection techniques including observation, interviews, and documentation. The researcher employed data analysis techniques involving data reduction, data presentation, and conclusion drawing. The results of this study indicate that the process of implementing the transition from the 2013 Curriculum to the Merdeka Curriculum in the history subject has been quite in line with the guidelines of the Ministry of Education and Culture, including understanding the Merdeka Curriculum, building readiness, planning the transition implementation, carrying out the implementation, conducting evaluation, and making revisions. This study offers novelty in the context of education policy implementation, particularly in the transition from the 2013 Curriculum to the Merdeka Curriculum in history subjects at the senior high school level.